(2x-2)2=(3x-2)(x-3)

Simple and best practice solution for (2x-2)2=(3x-2)(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-2)2=(3x-2)(x-3) equation:


Simplifying
(2x + -2) * 2 = (3x + -2)(x + -3)

Reorder the terms:
(-2 + 2x) * 2 = (3x + -2)(x + -3)

Reorder the terms for easier multiplication:
2(-2 + 2x) = (3x + -2)(x + -3)
(-2 * 2 + 2x * 2) = (3x + -2)(x + -3)
(-4 + 4x) = (3x + -2)(x + -3)

Reorder the terms:
-4 + 4x = (-2 + 3x)(x + -3)

Reorder the terms:
-4 + 4x = (-2 + 3x)(-3 + x)

Multiply (-2 + 3x) * (-3 + x)
-4 + 4x = (-2(-3 + x) + 3x * (-3 + x))
-4 + 4x = ((-3 * -2 + x * -2) + 3x * (-3 + x))
-4 + 4x = ((6 + -2x) + 3x * (-3 + x))
-4 + 4x = (6 + -2x + (-3 * 3x + x * 3x))
-4 + 4x = (6 + -2x + (-9x + 3x2))

Combine like terms: -2x + -9x = -11x
-4 + 4x = (6 + -11x + 3x2)

Solving
-4 + 4x = 6 + -11x + 3x2

Solving for variable 'x'.

Reorder the terms:
-4 + -6 + 4x + 11x + -3x2 = 6 + -11x + 3x2 + -6 + 11x + -3x2

Combine like terms: -4 + -6 = -10
-10 + 4x + 11x + -3x2 = 6 + -11x + 3x2 + -6 + 11x + -3x2

Combine like terms: 4x + 11x = 15x
-10 + 15x + -3x2 = 6 + -11x + 3x2 + -6 + 11x + -3x2

Reorder the terms:
-10 + 15x + -3x2 = 6 + -6 + -11x + 11x + 3x2 + -3x2

Combine like terms: 6 + -6 = 0
-10 + 15x + -3x2 = 0 + -11x + 11x + 3x2 + -3x2
-10 + 15x + -3x2 = -11x + 11x + 3x2 + -3x2

Combine like terms: -11x + 11x = 0
-10 + 15x + -3x2 = 0 + 3x2 + -3x2
-10 + 15x + -3x2 = 3x2 + -3x2

Combine like terms: 3x2 + -3x2 = 0
-10 + 15x + -3x2 = 0

Begin completing the square.  Divide all terms by
-3 the coefficient of the squared term: 

Divide each side by '-3'.
3.333333333 + -5x + x2 = 0

Move the constant term to the right:

Add '-3.333333333' to each side of the equation.
3.333333333 + -5x + -3.333333333 + x2 = 0 + -3.333333333

Reorder the terms:
3.333333333 + -3.333333333 + -5x + x2 = 0 + -3.333333333

Combine like terms: 3.333333333 + -3.333333333 = 0.000000000
0.000000000 + -5x + x2 = 0 + -3.333333333
-5x + x2 = 0 + -3.333333333

Combine like terms: 0 + -3.333333333 = -3.333333333
-5x + x2 = -3.333333333

The x term is -5x.  Take half its coefficient (-2.5).
Square it (6.25) and add it to both sides.

Add '6.25' to each side of the equation.
-5x + 6.25 + x2 = -3.333333333 + 6.25

Reorder the terms:
6.25 + -5x + x2 = -3.333333333 + 6.25

Combine like terms: -3.333333333 + 6.25 = 2.916666667
6.25 + -5x + x2 = 2.916666667

Factor a perfect square on the left side:
(x + -2.5)(x + -2.5) = 2.916666667

Calculate the square root of the right side: 1.707825128

Break this problem into two subproblems by setting 
(x + -2.5) equal to 1.707825128 and -1.707825128.

Subproblem 1

x + -2.5 = 1.707825128 Simplifying x + -2.5 = 1.707825128 Reorder the terms: -2.5 + x = 1.707825128 Solving -2.5 + x = 1.707825128 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 1.707825128 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 1.707825128 + 2.5 x = 1.707825128 + 2.5 Combine like terms: 1.707825128 + 2.5 = 4.207825128 x = 4.207825128 Simplifying x = 4.207825128

Subproblem 2

x + -2.5 = -1.707825128 Simplifying x + -2.5 = -1.707825128 Reorder the terms: -2.5 + x = -1.707825128 Solving -2.5 + x = -1.707825128 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -1.707825128 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -1.707825128 + 2.5 x = -1.707825128 + 2.5 Combine like terms: -1.707825128 + 2.5 = 0.792174872 x = 0.792174872 Simplifying x = 0.792174872

Solution

The solution to the problem is based on the solutions from the subproblems. x = {4.207825128, 0.792174872}

See similar equations:

| 24+2x-x^2= | | 132-6x=2x-20 | | 12x-5=8x-x | | x(p-cv)=cf | | 4t-3=-13-2t | | 5.3+9.2x=7-4x-8.8 | | 1.8x+4.1x=5.7 | | 3.44-1.25=1.05(2.38x+6.81) | | 42x^2+10x=0 | | b=7x(-7) | | -3(2.47+1.25)=9.82 | | b=2x(-3) | | b=-2-4x(-3) | | E=-28+(5-2)*(-4) | | 3x+5=8-7x | | 35.13x-7.26=11-14.91x | | c=-22+(13-5)x(-5) | | y+11=15 | | -22+(13-5)x(-5)= | | 150+x+400=5000 | | 209-6x=30x+21 | | 2000=n(725-420) | | 8r+1=9 | | 4x+14=-19-7x | | 2x(3-x)=5x+7 | | x-2y=-26 | | -19x-21=80 | | 2x+9=7x-4 | | 7(t-2)-2=4 | | 900+x+65=1053 | | V=3.14*7*7*7 | | Y=x^2+2x-30 |

Equations solver categories